Potent anti-biofilm properties of plumbagin against fluconazole-resistant Candida auris - Hye-Won Jin; Yong-Bin Eom (Journal of Traditional and Complementary Medicine)
Background and aim: The escalation of fungal infections is driving an increase in disease and mortality rates. In particular, the emergence of Candida auris (C. auris), which shows powerful resistance to the antifungal drug fluconazole, is becoming a global concern. Furthermore, several biological hurdles need to be overcome by candidate therapeutics because C. auris has the ability to form biofilm. Therefore, this study aimed to investigate the antifungal and anti-biofilm effects of plumbagin, a natural extract, against fluconazole-resistant C. auris (FRCA). Experimental procedure: The minimum inhibitory concentrations (MICs) of fluconazole and plumbagin were determined against clinically isolated C. auris. Inhibition of biofilm formation and eradication effects of plumbagin against FRCA were confirmed through minimum biofilm inhibition concentration (MBIC) and minimum biofilm eradication concentration (MBEC) assays. Additionally, the inhibition of metabolic activity in biofilm cells was verified through quantification by XTT reduction assay and visualization by confocal laser scanning microscopy (CLSM). The relative expression levels of the azole resistant gene ERG11, the efflux pump gene CDR1, and the extracellular matrix gene KRE6, were measured. Results and conclusion: Plumbagin exhibits antifungal efficacy against C. auris and has been shown to effectively inhibit both the formation and eradication of biofilms produced by FRCA. Furthermore, the metabolic activity inhibition in biofilm cells was both quantified and visually observed. The downregulation of all genes (ERG11, CDR1, and KRE6) by plumbagin was confirmed. Taken together, this study demonstrates that plumbagin has antifungal and anti-biofilm efficacy against FRCA, indicating its potential as an alternative to antifungal agents and a valuable resource in combating FRCA infections.